2018
DOI: 10.1111/ijlh.12784
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐analytical stability of coagulation parameters in plasma stored at room temperature

Abstract: Overall, compared to the limits given by the current CLSI guidelines, for most coagulation parameters investigated in this study a longer storage period could be accepted. Time intervals for FVIII and FV dosage were shorter than recommended by the CLSI guidelines. For PT determination, our findings were consistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 20 publications
(106 reference statements)
7
32
2
1
Order By: Relevance
“…According to The Clinical and Laboratory Standards Institute (CLSI), the French Study Group on Hemostasis and Thrombosis (GFHT) and European Concerted Action on Thrombosis (ECAT), specimens kept at room temperature (15°C-25°C) for routine haemostasis tests or determination of coagulation factors should be analyzed within 4 hours of collection, except for the quick time (TQ), which has a stability of up to 24 hours, and tests to monitor treatment with unfractionated heparin, for which the delay should not exceed 2 hours [17,18]. Several studies have demonstrated longer stability for many hemostasis parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to The Clinical and Laboratory Standards Institute (CLSI), the French Study Group on Hemostasis and Thrombosis (GFHT) and European Concerted Action on Thrombosis (ECAT), specimens kept at room temperature (15°C-25°C) for routine haemostasis tests or determination of coagulation factors should be analyzed within 4 hours of collection, except for the quick time (TQ), which has a stability of up to 24 hours, and tests to monitor treatment with unfractionated heparin, for which the delay should not exceed 2 hours [17,18]. Several studies have demonstrated longer stability for many hemostasis parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated longer stability for many hemostasis parameters. This can be interesting, for example, when additional coagulation tests are requested or when laboratories must subcontract coagulation tests to a laboratory remote from the sampling site [2,[17][18][19]. However, further studies are needed to confirm the validity of this eventuality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLSI guideline is very strict, demanding all coagulation tests to be centrifuged and analyzed within 4 h, except PT-INR within 24 h and APTT with unfractionated heparin treatment within 2 h, but also states that longer storage time could be used if this is validated in one's own laboratory [7]. There are studies indicating that both PT-INR and fibrinogen are stable for 48 h and APTT for 24 h, both in citrated blood and plasma [5,6]. PT-INR and fibrinogen have even been shown to be stable for up to 72 h [27] and 7 days [28], respectively.…”
Section: Sample Stability and Storagementioning
confidence: 99%
“…In the case of insufficient mixing a clot could be formed in the sample [3]. Underfilled tubes or prolonged storage before testing may lead to a decrease of coagulation factor activities or altered impression of the anticoagulant effect in a monitoring situation [4][5][6][7]. In these circumstances, results would represent the situation in vitro and not in vivo.…”
Section: Introductionmentioning
confidence: 99%